2016
DOI: 10.1186/s12863-015-0308-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequent variations in cancer-related genes may play prognostic role in treatment of patients with chronic myeloid leukemia

Abstract: BackgroundGenome variability of host genome and cancer cells play critical role in diversity of response to existing therapies and overall success in treating oncological diseases. In chronic myeloid leukemia targeted therapy with tyrosine kinase inhibitors demonstrates high efficacy in most of the patients. However about 15 % of patients demonstrate primary resistance to standard therapy. Whole exome sequencing is a good tool for unbiased search of genetic variations important for prognosis of survival and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
0
17
3
Order By: Relevance
“…Among the non-syndromic genes, we noted DNAH9 with variants in three families, a gene that interacts with the hematopoietic regulator BCL6 48 and is also mutated in one of the families described by Churpek et al 40 . In another family we identified a variant in SH2B3 (p.Ala49Thr), implicated in hematopoietic stem cell self-renewal and quiescence through direct interaction with JAK2 [49][50][51] , with the variant adjacent to a frameshift variant described by Bluteau et al 42 (p.Arg50-Glyfs*147) (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Among the non-syndromic genes, we noted DNAH9 with variants in three families, a gene that interacts with the hematopoietic regulator BCL6 48 and is also mutated in one of the families described by Churpek et al 40 . In another family we identified a variant in SH2B3 (p.Ala49Thr), implicated in hematopoietic stem cell self-renewal and quiescence through direct interaction with JAK2 [49][50][51] , with the variant adjacent to a frameshift variant described by Bluteau et al 42 (p.Arg50-Glyfs*147) (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Direct DNA Sanger sequencing of PCR products was performed as described previously [ 13 ]. Briefly, DNA from peripheral blood samples was obtained from CML patients before TKI therapy.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of polymorphisms and mutations in genes associated with TKI resistance was reported [ 10 12 ]. Recently we have performed whole-exome sequencing in primary CML patients before TKI administration and revealed five genetic variants typical for optimal responders (rs11579366 in ANKRD35 , rs1990236 in DNAH9 , rs176037 in MAGEC1 , rs10653661 in TOX3 , rs3803264 in THSD1 ) and two – for non-optimal responders (rs3099950 in MORN2 , rs9471966 in PTCRA ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The paper of Lavrov and co-authors titled "Frequent variations in cancer-related genes may play prognostic role in treatment of patients with chronic myeloid leukemia" convincingly demonstrated that the gene variants present or absent in the genome of patient influence relative efficiency of the therapy for chronic myeloid leukemia, thus, paving a way to personalized approach to the treatment of this disease [4].…”
Section: Bmc Geneticsmentioning
confidence: 99%